Diagnosis of incarcerated intramesosigmoid hernia aided by multiplanar reconstruction images of multidetector computed tomography: a case report - Hideki Nagano; Takanori Goi; Seiichi Taguchi; Takayoshi Tsubaki; Hidemasa Uematsu (Surgical Case Reports, 2018)
Abstract Background Internal hernia is a rare cause of intestinal obstruction, and sigmoid mesocolon hernia is an extremely rare form of this condition. Among sigmoid mesocolon hernias, intramesosigmoid hernia is the least frequent subtype. We described a case of intramesosigmoid hernia through the orifice on the right leaf of the mesosigmoid with an incarcerated ileum of 6 cm in length without strangulation. This case was diagnosed by multidetector computed tomography with multiplanar reconstruction images and treated without resection of the small intestine in a 52-year-old man with characteristic diagnostic images. Case presentation A 52-year-old man suffering periumbilical cramping pain with sudden onset that had persisted for 1 week without recovery was referred to Fukui Katsuyama General Hospital. Multidetector computed tomography revealed small bowel obstruction, and an incarcerated short intestinal loop was revealed by sagittal slices of the multiplanar reconstruction images of the routine study of the left side of the pelvic space. Sagittal multiplanar reconstruction images also showed narrow belt-shaped fluid retention contacting the tip of the incarcerated short loop toward the cranial direction localized in the mesosigmoid. These findings indicated that the fluid and the herniated small bowel were wrapped together in the mesosigmoid, which was characteristic of intramesosigmoid hernia. The patient underwent laparotomy operation 2 days after admission. The ileum, which was approximately 75 cm proximal to the ileocecal junction and herniated into the mesosigmoid through the right leaf, was released without resection. The orifice located in the central part of the right leaf was oval shaped and measured less than 2 cm in diameter. The left leaf of the mesosigmoid was intact. The orifice of the right lobe was closed by suture. The patient showed an uneventful recovery. Conclusion We report an extremely rare case of incarcerated intramesosigmoid hernia that was diagnosed by multidetector computed tomography with multiplanar reconstruction images. The finding of narrow belt-shaped fluid retention contacting the tip of the incarcerated short intestinal loop is characteristic of intramesosigmoid hernia and will be useful for conclusively differentiating this disease from transmesosigmoid hernia. Although intramesosigmoid hernia is a rare cause of internal hernia, multidetector computed tomography and multiplanar reconstruction images can provide the characteristic findings and proved useful for the precise preoperative diagnosis and treatment of intramesosigmoid hernia.